Triaza-based amphiphilic chelators : synthetic route, in vitro characterization and in vivo studies of their Ga(III) and Al(III) chelates - Sá, Arsénio Vasconcelos (2010)
Radiogalium chelates are important for diagnostic imaging in nuclear medicine (PET and ƴ-scintigraphy). Micelles are adequate colloidal vehicles for the delivery of therapeutic and diagnostic agents to organs and tissues. In this paper we describe the synthesis and in vitro and in vivo studies of a series of micelles-forming Ga(III) chelates targeted for the liver. The amphiphilic ligands are based on NOTA (NOTA = 1,4,7-triazacyclonoane-N,N’N’’-triacetic acid) and bear a α-alkyl chain in one of the pendant acetate arms (the size of the chain changes from four to fourteen carbon atoms). A multinuclear NMR study (1H, 13C, 27Al and 71Ga) gave some insights into the structure and dynamics of the metal chelates in solution, consistent with their rigidity and octahedral or pseudo-octahedral geometry. The critical micellar concentration of the chelates was determined using a fluorescence method and 27Al NMR spectroscopy (Al(III) was used as a surrogate of Ga(III)), both showing similar results and suggesting that the chelates of NOTAC6 form pre-micellar aggregates. The logP (octanol-water) determination showed enhancement of the lipophilic character of the Ga(III) chelates with the increase of the number of carbons in the α-alkyl chain. Biodistribution and Ƴ-scintigraphic studies of the 67Ga(III) labeled chelates were performed on Wistar rats, showing higher liver uptake for [67Ga](NOTAC8) in comparison to [67Ga](NOTAC6), consistent with a longer α-alkyl chain and a higher lipophilicity. After 24 hours both chelates were completely cleared off from the tissues and organs with no deposition in the bones and liver/spleen. [67Ga](NOTAC8) showed high kinetic stability in blood serum.